A feasibility study on TreatCo. Inc.'s coco peat mining wastewater treatment system - Cano, Marionne Rose; Divinagracia, Derrick Jan; Juanatas, Pamela Rae; Villanueva, Thea
Executive Order 79 (EO 79), passed by President Benigno Aquino Jr., ensures environmental protection and responsible mining in the utilization of mineral resources by providing policies and guidelines and implementing reforms in the Philippine mining sector. With regards to the small-scale mining (SSM) industry, this means a complete and total ban of the use of mercury for ore processing. With the implementation of EO 79, SSM operators are obligated to register their activities with the Department of Environment and Natural Resources (DENR). Unfortunately, not all SSM operators do so; it is estimated that there are around 100,000 existing SSM operations in the Philippines. The Coco Peat System functions as an alternative wastewater treatment system for indigenous persons who practice mining without the use of heavy equipment or explosives, and utilizes simple techniques for ore extraction and processing. Its main component, coco peat, has been proven to 6e a good absorber of heavy metal tailings from mining effluents. The number of SSM operators is estimated to increase by 1.54 % per year. This is based from the average yearly production change recorded by the DENR from 2008 to 2011. With a targeted market-capture percentage of 300k for registered SSMs and 20% for unregistered SSMs over the next five years, the Coco Peat System is expected to service up to 21,000 SSMs in total. The coco peat system will be sold at a retail price of Php3,000 per unit; a discounted price of PhpS,200 will be offered if two units are to be purchased simultaneously. Phpl,200 will be charged for every replacement service, which is estimated to be necessary every 3 months. The first two years will see the establishment of one facility in Bukidnon (Mindanao), followed by service centers in Bacolod City (Visayas) and Quezon province {Luzon) in years 3-5. Transportation of system components and layers needed for replacement is determined. The company has decided to purchase trucks instead of outsourcing its transportation needs. This is due to the requirement that assembly men accompany products for installation. Transportation costs are computed through cost estimates provided by a trucker for 250-300KM distances (in which the average of 274KM falls). The workforce requirement for the next five years is determined in conjunction with the estimated increase in target share, as well as the projected market share capture. The layout of the facility allots 0.2 cubic meters per unit of the pre-assembled system components. Suppliers shall be sourced per local region, with the exception of the HOPE containers-which shall be sourced from a single supplier. The purchasing of raw materials is planned according to capacity and forecasted demand. with stock assumptions {40% to avail of price package; 60% to purchase a single unit; 100% to avail of service replacements) to account for periods of unforeseen demands and additional maintenance needs. The company shall be using debt and equity as its sources of funds to enable operations in 2013. The 80-20 ratio shall be applied since listing the company in the stock market requires evidence of performance to attract investment; 20% of the working capital shall be generated through debt. A capital of Php 27,614,870 should be available to cover capital expenditure costs, initialization costs, and operating expenses for the i" year. The amount of Php20 M is deemed to be the appropriate amount that must be obtained by the company through equity and debt financing. A loan is to be obtained from the GSIS Special Financing Program; it terms include an interest rate of 12%, with a payment period of 5 years. An additional loan of Php 7.5 M shall be obtained in the 2°d year through the same program to cover for the expansion expense requirements for the 3'd year. Results of the analysis show that the company is financially feasible; the downtrends in generated accounting statements are reflections of capital expenditure, operating and other initialization expenses incurred by the company in its start-up and expansion years. The change in price is seen to affect the company's profitabillty at a higher rate than the change in cost of raw materials. Consequently, price increases and market changes should be monitored, as this may significantly affect the company's financial performance. Contingency measures, such as increasing loan amounts or equity requirements, can offset the effect of these changes-unless income in the following years is not able to show a consistent positive trend. Nonetheless, the company expects a positive income and financial performance in the subsequent years. The benefits of introducing the Coco Peat Filtration System to the market far outweigh the costs of operations for the first 5 years. With a benefit/cost ratio of 1.16, the project is deemed socially feasible. The system is seen to provide employment opportunities and additional revenues to suppliers and government entities. Additionally, other non-quantifiable benefits, such as reduction in water pollution from mining operations, are expected to rise over time once the business overcomes its start-up phase.